Evaluation of School Canteen Hygiene Implementation Based on Administrative Data at LPI Assalam Rimbo Bujang - nurcihikita, Tiara; Afriza, Zakya; Hania, Anggun Putri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, Universitas Muhammadiyah Muara Bungo, 2025)
This study evaluated the implementation of school canteen hygiene at LPI Assalam Rimbo Bujang based on available administrative data. Canteen hygiene plays a crucial role in preventing foodborne diseases and maintaining student health; however, the utilization of administrative data as a monitoring and evaluation tool is often suboptimal. The research employed a descriptive-evaluative method with a quantitative approach, focusing on analyzing administrative data from daily cleanliness forms, inspection reports, and other relevant documents within a specific period. The results indicate that the availability and completeness of administrative data varied, but it could provide insights into the level of canteen hygiene compliance, covering environmental cleanliness, personal hygiene of staff, food handling, and waste management. Gaps in recording consistency were identified, which impacted the accuracy of the evaluation. In conclusion, administrative data serve as a vital source of information for monitoring canteen hygiene implementation. Improving structured recording systems and continuous training for canteen staff and relevant parties are highly recommended to optimize canteen hygiene and sanitation management, thereby ensuring food safety and student health at LPI Assalam Rimbo Bujang. Keywords: School Canteen Hygiene, Administrative Data, Health Management in Schools, Food Safety